Arabic Learning for Elementary School during COVID-19 Emergency in Indonesia - Suci Ramadhanti Febriani; Rizka Widayanti; Muhammad Afif Amrulloh; Nuril Mufidah (OKARA: Jurnal Bahasa dan Sastra, 2020)
Arabic language learning in the era of the COVID-19 emergency requires a good learning design. This research aims to ascertain how the Arabic learning process is done online at SDIT Al-Azhar Padang; how the students' responses; and the obstacles faced by teachers when teaching Arabic by online in the COVID-19 emergency. This study used a qualitative approach with a case study research design. The data collection included observation, interviews, and documentation with data analysis techniques by using data triangulation. The results showed that; 1) the Arabic learning model in the era of COVID-19 emergency can be done by integrating media, material, and evaluation based on online 2) the improvement of students' motivation and their interest in learning online can be seen with the indications that students were fast in responding and they got the maximal results in Arabic learning, 3) some of the obstacles faced by teachers when the online learning is done are the limited ability of teachers to design the material, unlimited time allocation, lack of communication to explain the detailed instruction. The findings found that Arabic learning online can encourage creativity, critical thinking skills, good communication, and the ability to process information based on technology.